Impact of workplace bullying on organizational outcome - Shehnaz Bano; Sadia Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This research examines the impact of workplace bullying on organization related outcomes among Doctors. By using purposive sampling technique, data was obtained from 200 male and female doctors having age range from 23 to 45 years. The sample was obtained from 7 different public and private hospitals of Lahore city. NAQ-R scale by Einarsen et al. (2009), job related affective well being scale by Van Katwyk et al. (2000), overall Job satisfaction scale by Cook et al. (1981) and organizational-based self esteem scale by Pierce et al. (1989) were separately used to measure workplace bullying and organization related outcomes. The findings indicate that workplace bullying is strong predictor of lower job affective well being and job satisfaction. The findings of this research have implications for increasing our awareness of the actions and behaviors of workplace bullies and to introduce preventive measures for secure and good workplace settings for all workers.
Keywords: 330; workplace bullying; organizational outcome; doctors; hospitals